The Principles of the Issue of Resurrection According to the Propositions of Muslim Thinkers - Abdullah HosseiniEskandian; Ali Babaei (Universitas Negeri Jakarta, 2024)
The issue of resurrection is one of the basic principles of divine religions that all the divine prophets had the mission to invite people to believe in the Day of Judgment after being called to worship the Only God. Among the divine religions, Islam has shown special attention to the question of resurrection and this basic principle has been discussed and pondered by many Muslim thinkers. In addition to the religious aspect, the issue of resurrection is of fundamental importance since the general nature of the human race is mixed with it and humans tend towards happiness and good fortune. In this article, an attempt is made to investigate the importance and necessity of the issue of resurrection, the nature of resurrection, the types of resurrection, the questions of resurrection and its proof based on the Islamic perspective, using a descriptive-analytical method. Apart from all the proofs that have been established to prove the issue of resurrection, it can be stated that human nature tends to an end beyond this material world that does not see himself limited in this world and sees a world beyond this material world in his horizon.